Research and Analytical Study of the Thoughts of Imam Ibn Taymiyyah about Apostasy - Ahmad, Hafiz Noman (Journal of Islamic and Religious Studies, 2022)
After accepting Islam, it is prohibited for any person to abandon Islam and convert to another religion or to adhere to certain principles and acts of worship but rejecting certain other manifest, or consistently proven principles and acts of worship. Ibn Taymiyyah was one of the most popular figures and a talented writer in Islamic history. He has written in detail about apostasy in his literature and mentioned the principles, conditions and manners related to it. In the contemporary era, some resistance and jihadist military movements, in the name of Islamic Jihad, declare all the rulers of the Islamic world and those who support them as apostates for imitating the prevailing political and democratic system and declare their murder obligatory. And connect this violent behavior with the thoughts of Ibn Taymiyyah. Although the fatwas of apostasy issued by militant or jihadi groups against the Muslim people, rulers, officials, political system, and democratic government, is a misinterpretation of Ibn Taymiyyah's fatwas and ignorance of the true spirit of his fatwas. In this situation, there is an urgent need to know and study Ibn Taymiyyah's thoughts and ideas to know his point of view regarding apostasy and the true spirit of his fatwa to end the current terrorism.